Transient stability analysis of the IEEE 39-bus test system using Dynamic Computation for Power Systems (DCPS): article - Arshad, Nor Hasimah (2010)
Transient stability analysis (TSA) plays an important role for maintaining security of power system operation. This paper covers the transient stability analysis using Dynamic Computation for Power Systems (DCPS) software. The general purpose of DCPS is as simulation program of power system to implement the algorithms described. Immediately after a disturbance, one is concerned with the system's ability to reach an acceptable steady-state operating condition. This is called transient stability. Transient stability occurs when the power system is able to withstand the transient conditions following a major disturbance or fault which may lead to harm the system. Therefore determination of critical clearing time (CCT) is crucial since such information enables the setting of relays to clear the fault for the protection. Definition for critical clearing time is a maximal fault duration for which the system remains transiently stable. This paper also analyzes the CCT of fault occurrence between transmission line near to the reference bus and far from the reference bus. By theory CCT should appears to be lesser when fault occurs at transmission line near to the reference bus. In addition, this investigation is also to analyze the characteristics of transient stability when fault occur at swing bus. The stability of the system has been observed based on the simulation graphs of terminal voltage of the machine, rotor angle, speed, and output electrical power.